The Anti-civic Effects of Popular Culture on American Teenagers - Anders Lewis; Jennifer Butler; Melanie Winklosky; Sandra Stotsky (Universidad de Navarra, 2018)
Civic participation and civic awareness is essential to the maintenance of American democracy. Strong civic communities serve to promote prosperity, ensure the resolution of collective problems, and act as a check upon the power of the state. But in 2002, there is little doubt that, across a wide range of indicators, America's civic culture is in decline. Voting rates have fallen rapidly over the past several decades, and so too has trust in government. Equally troubling is the disconcerting dearth of civic knowledge among American youths and the drop in participation, among all Americans, in numerous civic organizations, from church-affiliated groups to voluntary and fraternal organizations as well as women's auxiliaries and unions. There are many causes for these trends. This paper examines how popular culture affects civic participation and civic awareness among a group of particularly active teenagers in Massachusetts. We found that popular culture has a generally negative influence on civic life but that its effects are not one-sided and that it can be mitigated by strong families and quality schools committed to an academic and civic education